If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2n + y + z = 0 Solving 2n + y + z = 0 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-1y' to each side of the equation. 2n + y + -1y + z = 0 + -1y Combine like terms: y + -1y = 0 2n + 0 + z = 0 + -1y 2n + z = 0 + -1y Remove the zero: 2n + z = -1y Add '-1z' to each side of the equation. 2n + z + -1z = -1y + -1z Combine like terms: z + -1z = 0 2n + 0 = -1y + -1z 2n = -1y + -1z Divide each side by '2'. n = -0.5y + -0.5z Simplifying n = -0.5y + -0.5z
| A=18/2(74) | | 4=25-7g | | 2.1-.6y=.9 | | N/16=-8 | | u^2-5u-35=0 | | 5r+45/3r-18 | | A=18/2x74 | | X+2x+14=5x+19 | | x^2-3y^2-14x+2y+6=0 | | 3(1-8x)=4x-37 | | 26/7f=1/3 | | 6.25x+7.5-2.5x=3.75x-8.75 | | 256=4y | | p-4=-9p+p | | 2x^4-40x^2+38=0 | | 4t^2-2t/2t | | 15(3+x)=90 | | 6(4-z)=18 | | 8x^3-192x^4+1536x^3-4096x^2=0 | | 52.50=0.25x+15 | | 2x^3+x^2-6x-1040=0 | | A=1/2(24)(74) | | w^2+16w=260 | | 4x-3y+7=0 | | 2x^2-6x-32=0 | | xdy-ydx+(y^2-1)dy=0 | | (2+-5)(2+-1)=0 | | (4x+49)=(8x+5) | | 3w^2-21=0 | | 3v-12=168 | | n=(-p+5x)/-5 | | 4x+30=45x |